Cinnamomum zeylanicum (Ceylon cinnamon) as a potential pharmaceutical agent for type-2 diabetes mellitus: study protocol for a randomized controlled trial - Priyanga Ranasinghe; Priyadarshani Galappaththy; Godwin Roger Constantine; Ranil Jayawardena; Hasitha Dhananjaya Weeratunga; Sirimal Premakumara; Prasad Katulanda (Trials, 2017)
Abstract Background Previous studies have explored the anti-diabetic effects of Cinnamomum cassia extract in vivo and in vitro. However, there are no studies at present exploring the effects of the indigenous species of Sri Lankan cinnamon (Cinnamomum zeylanicum) in patients with diabetes mellitus. The present study aims to evaluate the potential effects of Cinnamomum zeylanicum extract as a pharmaceutical agent in patients with type-2 diabetes mellitus. Methods/design The study will be conducted as a randomized, double-blind, placebo-controlled clinical trial for a period of 4 months at the Medical Clinic, University Medical Unit, National Hospital of Sri Lanka. A total of 210 subjects with diabetes, in three equal groups, will be recruited for the study. The patients will be randomized in a 1:1:1 ratio according to the method of block randomization and the subjects will be randomly and equally assigned into two test groups (n = 70 each) and one placebo group (n = 70). The population will be stratified at randomization based on age, gender and disease severity. The treatment drug is a capsule containing Cinnamomum zeylanicum extract as the active ingredient and the placebo capsule will contain lactose monohydrate. Two doses of Cinnamomum zeylanicum extracts (250 mg and 500 mg of the cinnamon extract) will be used. The study drugs will be double blinded to both investigators and participants. The visits and the evaluations will be done as follows: screening (visit 0), 1 month (visit 1), 2 months (visit 2), 3 months (visit 3) and 4 months (visit 4). The following primary outcome measures will be evaluated: glycosylated hemoglobin (HbA1c), fasting plasma glucose (FPG) and serum insulin. Secondary outcome measures include: Body Mass Index (BMI) and other anthropometric parameters, blood pressure, total cholesterol, low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL) and triglycerides (TAG). Data will be analyzed using SPSS version 14. Discussion We describe the protocol for a clinical trial design evaluating the effects of Cinnamomum zeylanicum (Ceylon cinnamon) in patients with type-2 diabetes mellitus. The result of the present study, positive or negative, should provide a step change in the evidence guiding current and future policies regarding the use of cinnamon dietary supplementation in patients with diabetes. Trial registration Sri Lanka Clinical Trials Registry (SLCTR), identifier: SLCTR/2017/010 ( http://slctr.lk/trials/714 ). Registered on 5 April 2017; study protocol version 3.1 21 March 2017.